Correlation Between Duration Of Protease Inhibitor Therapy With Insulin Resistance In HIV Patients - Nasution, M. Arif Habibi; Nasution, Melati Silvanni; Dian Anindita Lubis (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Abstract Metabolic diseases related to Human Immunodeficiency Virus (HIV) caused an increase in the workload of health services. Prevalence of HIV infection in Indonesian provinces varied considerably, ranging from less than 0.1% to 4%. Several studies have analyzed the correlation between insulin resistance and the usage of antiretroviral drugs, especially protease inhibitors. The main mechanism that responsible for insulin resistance is related to glucose transporter inhibition (GLUT4). This study objective is to assess the correlation between prolonged administration of protease inhibitors and insulin resistance in patients with that have diagnosed with HIV. Method. This research is an observational research using a cross-sectional design. The study was carried at the POSYANSUS Polyclinic at H. Adam Malik General Hospital in August - December 2019. The study sample were 34 HIV-treated patients receiving protease inhibitor ARV therapy. The study was analysed using chi square. Results. The characteristics of the study subjects had the most frequent age range at the age of 34 - 49 years (54.3%), men (71.4%) and women (28.6%). The longest use of antiretroviral drugs is most in the 6-12 months group (60%). Insulin resistance number in this study was 13 people (37.1%). The average HOMA-IR value of the study subjects was 2 (0.8-16.5), fasting blood sugar levels were 86 (70-283) mg / dl, fasting insulin levels were 9.1 (4.1-79.4) (µU / ml)., urea levels of 20.88 ± 9.7 mg / dl and creatinine levels of 0.81 ± 0.15 mg / dl. There was a significant correlation between the duration of ARV treatment with insulin resistance (p = 0.018; OR 7.65) Conclusion. There is a significant correlation between the duration of ARV treatment with insulin resistance. The longer Protease Inhibitor was used, the bigger insulin resistance.